Group approach for enhancing profitability of small holders through technology integration-reflections from coconut farming - Thamban, C.; Subramanian, P.; Jayasekhar, S.; Jaganathan, D.; Muralidharan, K. (Journal of Plantation Crops, 2017)
Technology integration for enhancing productivity and income from coconut farming, facilitated through stakeholder participation, was a major objective of the NAIP sub-project on ‘Value chain in coconut’ implemented in a consortium mode with ICAR-Central Plantation Crops Research Institute, Kasaragod as the lead institute. To achieve this objective, 10 clusters of coconut farmers were formed under the project in selected panchayats of Kasaragod district in Kerala state. A total of 534 farmers covering 250 ha participated in the project interventions. Appropriate production technologies were integrated in their holdings which included intercropping, growing of leguminous crops in the coconut basin, organic recycling through vermicomposting and integrated nutrient management. Group action was initiated among the farmers for taking up need-based integrated disease management measures especially to control bud rot disease of coconut. Knowledge and skill upgradation of farmers on the selected technologies were achieved through various institutional and off campus training programmes. The net income from the coconut farming in small and marginal holdings could be increased through the interventions under the project. Technology integration in the holdings also resulted in the increase of coconut productivity from 60 to 112 nuts per palm. Technology integration in small and marginal coconut holdings for higher productivity and income through Community Based Organizations approach is scaled up by other agencies like Coconut Development Board for implementing development/extension programmes.